The Efficiency of Chitosan Against Tert Butylhydroquinone (TBHQ)-Induced Neurobehavioral Changes and Toxicity Effects in Male Rats - Shahad Alahmadi; Mohammed Mufadhe Alanazi; Fawaz Alasmari; Wedad Saeed Al-Qahtani; Gadah Albasher (Frontiers in Bioscience-Landmark)
Background: We investigated chitosan’s protective effects against tertiary butylhydroquinone (TBHQ)-induced toxicity in adult male rats, focusing on cognitive functions and oxidative stress in the brain, liver, and kidneys. Methods: Rats were divided into four groups (n = 8/group): (1) Control, (2) Chitosan only, (3) TBHQ only, and (4) Chitosan + TBHQ. Results: TBHQ exposure led to significant cognitive impairments and increased oxidative stress, marked by elevated malondialdehyde (MDA) and decreased superoxide dismutase (SOD) and glutathione (GSH) levels. Behavioral tests, including the Morris Water Maze (MWM) as well as Passive Avoidance Learning (PAL) tasks, confirmed memory and learning deficits in the TBHQ group. Histopathological analysis showed damage in the brain, liver, and kidney tissues of TBHQ-exposed rats. Chitosan treatment significantly mitigated these effects, reducing oxidative stress markers and preserving tissue integrity. These findings suggest that chitosan’s antioxidant properties may provide a therapeutic benefit against TBHQ-induced neurotoxicity and organ damage. Conclusions: These findings suggest that chitosan exerts potent neuroprotective effects, potentially through its antioxidant and anti-inflammatory properties, and could serve as a therapeutic agent against TBHQ-induced toxicity.